Optimization of cooling systems in data centre by computational fluid dynamics model and simulation - Romadhon, Rahmat; Ali, Maisarah; Mohd Mahdzir, Ayub; Abdalla Abakr, Yousif (2009)
Development of information technology drives the increase demand of data centre and the invention of high performance of computer facilities which will impact to the increasing of heat dissipation from equipment. The environmental condition in data centre must be designed and maintained strictly to avoid disruption and thermally shut down that caused by overheat and loss of cooling. This paper primarily focuses on the optimization cooling system in data centre by arrangement of racks position and airflow management. Models and simulation of Computational Fluid Dynamics (CFD) are developed for the room and equipment of data centre where the effect to temperature and airflow profiles will be observed. A case study of data centre design in Kuala Lumpur with 30 racks of equipment and combination of raised floor cooling and spot cooling was carried out. Results of CFD simulation show the issues of data centre cooling and improvement was suggested to improve the distribution of cooling and reduction of hot spots.